Comparação do efeito agudo da estimulação transcutânea auricular do nervo vago em dois locais diferentes sobre a pressão arterial e modulação autonômica cardíaca em indivíduos hipertensos: estudo clínico crossover randomizado duplo-cego - Venâncio, Bruno Paulino (2025)
Introduction: Arterial hypertension (AH) is a chronic condition characterized by persistently elevated blood pressure (BP), which can lead to target organ damage. Transcutaneous auricular vagus nerve stimulation (taVNS) has shown promise as an approach to reduce BP and improve cardiac autonomic balance. However, further studies are needed to determine optimal stimulation parameters to ensure its efficacy and safety. Objective: To compare the acute effect of taVNS on BP and heart rate variability (HRV) in hypertensive individuals, applied to two different sites of the auricular branch of the vagus nerve. Methods: Eighty-four hypertensive adults received one session of taVNS in the tragus, cymba conchae, and earlobe, with a one-week interval between sessions. Variables measured included systolic (SBP) and diastolic (DBP) blood pressure, heart rate (HR), peripheral oxygen saturation (SpO₂), an autonomic function test using handgrip strength, and HRV parameters such as high frequency, low frequency, low frequency/hight frequency, standard deviation of RR intervals, root mean square of successive differences, percentage of adjacent RR intervals differing by more than 50 ms, standard deviation 1, standard deviation 2, and sample entropy. Assessments were performed before, during, and after stimulation. Results: The results demonstrated that, at baseline, participants had sympathetic predominance and lower HRV, characterizing autonomic dysfunction. Stimulation of the cymba conchae significantly reduced (p<0.05) DBP and SBP compared to the other sites. However, no significant differences were observed between the stimulation sites in HRV parameters. Conclusion: The findings indicate that a single taVNS session is not sufficient to produce clinically relevant changes in autonomic function in hypertensive individuals, although cymba conchae stimulation showed more promising effects on blood pressure reduction. Further studies with longer protocols and more robust designs are needed to confirm and expand on these findings.